Penerapan Safe Place Technique Dalam Menurunkan Gejala Kecemasan Pada Anak Yang Mengalami Selective Mutism - Dyah Ageng Pramesty Koenarso (UIN Sultan Maulana Hasanudin Banten, 2020)
This research focus aimed to gain an overview of the application of safe place techniques in reducing anxiety symptom for children with selective mutism. This research was conducted in TA Zam-zam Kota Malang. This research used a qualitative research with a type of case study. The data analysis technique that used was Miles and Huberman model. Data were obtained from interview, observation and analysis documents. This re- search found that the intervention by the teacher on N showed that the implementation of the basic principles of safe place techniques is appropriate for N because it did not direct- ly focus on the problem of the rejection approach of speech experienced by children, this can be seen from the gesture of N who gradually began to open themselves to their sur- roundings. Children were not required to verbally express their feelings or emotions. Children's feelings and thoughts can be expressed through playing and drawing.